Effect of seasonal malaria chemoprevention plus azithromycin on Plasmodium falciparum transmission: gametocyte infectivity and mosquito fitness - Koudraogo Bienvenue Yaméogo; Rakiswendé Serge Yerbanga; Seydou Bienvenu Ouattara; Franck A. Yao; Thierry Lefèvre; Issaka Zongo; Frederic Nikièma; Yves Daniel Compaoré; Halidou Tinto; Daniel Chandramohan; Brian Greenwood; Adrien M. G. Belem; et al. (Malaria Journal, 2021)
Abstract Background Seasonal malaria chemoprevention (SMC) consists of administration of sulfadoxine-pyrimethamine (SP) + amodiaquine (AQ) at monthly intervals to children during the malaria transmission period. Whether the addition of azithromycin (AZ) to SMC could potentiate the benefit of the intervention was tested through a double-blind, randomized, placebo-controlled trial. The effect of SMC and the addition of AZ, on malaria transmission and on the life history traits of Anopheles gambiae mosquitoes have been investigated. Methods The study included 438 children randomly selected from among participants in the SMC + AZ trial and 198 children from the same area who did not receive chemoprevention. For each participant in the SMC + AZ trial, blood was collected 14 to 21 days post treatment, examined for the presence of malaria sexual and asexual stages and provided as a blood meal to An. gambiae females using a direct membrane-feeding assay. Results The SMC treatment, with or without AZ, significantly reduced the prevalence of asexual Plasmodium falciparum (LRT X2 2 = 69, P < 0.0001) and the gametocyte prevalence (LRT X2 2 = 54, P < 0.0001). In addition, the proportion of infectious feeds (LRT X2 2 = 61, P < 0.0001) and the prevalence of oocysts among exposed mosquitoes (LRT X 2 2 = 22.8, P < 0.001) was reduced when mosquitoes were fed on blood from treated children compared to untreated controls. The addition of AZ to SPAQ was associated with an increased proportion of infectious feeds (LRT X2 1 = 5.2, P = 0.02), suggesting a significant effect of AZ on gametocyte infectivity. There was a slight negative effect of SPAQ and SPAQ + AZ on mosquito survival compared to mosquitoes fed with blood from control children (LRTX2 2 = 330, P < 0.0001). Conclusion This study demonstrates that SMC may contribute to a reduction in human to mosquito transmission of P. falciparum, and the reduced mosquito longevity observed for females fed on treated blood may increase the benefit of this intervention in control of malaria. The addition of AZ to SPAQ in SMC appeared to enhance the infectivity of gametocytes providing further evidence that this combination is not an appropriate intervention.